Lo sviluppo del programma Galileo: sue traversie, lezioni e considerazioni - Caporale, Mario (GEOmedia, 2017)
This article sketches the European trail from conception to development of the Galileo system, highlighting the major steps, and trying to derive the lesson learned from the various experiences. The Galileo system represents the really first European programme, involving political, strategical, operational, industrial and technological aspects which challenge the European institution. The Galileo system permeates the European activities, challenges the international relations policy, constitutes a powerful instrument to verify and consolidate the European Union.